Kedudukan Ikatan Notaris Indonesia sebagai Organisasi Profesi untuk Profesi Notaris di Indonesia - Faisal Makna, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research method uses a type of normative juridical research, namely research that refers to legal norms or principles by studying and researching problems using various literature in the form of library materials or secondary data. As explained above, this research is normative legal research. Research is a tool used by humans. Based on the type of data used, it is general and specific in nature and then a conclusion can be drawn. First research result: that the Notary professional organization does not have to be single because in the provisions of Article 82 paragraph (1) of Law Number 2 of 2014 concerning the Position of Notaries states